Association of typical atrial flutter and cavotricuspid isthmus ablation on clinical recurrence after cryoballoon ablation for atrial fibrillation - Jeong, Joo Hee; Lee, Hyoung Seok; Choi, Yun Young; Kim, Yun Gi; Choi, Jong-Il; Kim, Young-Hoon; Lim, Hong Euy; Oh, Il-Young; Cha, Myung-Jin; Lee, So-Ryoung; Kim, Ju Youn; Kwon, Chang Hee; et al. (Frontiers in Cardiovascular Medicine, 2023)
Typical atrial flutter commonly occurs in patients with atrial fibrillation (AF). Little is known about the effects of concurrent atrial flutter on long-term outcomes of rhythm control. This study investigated the association between concurrent typical atrial flutter and cavotricuspid isthmus (CTI) ablation and the recurrence of atrial arrhythmia. Data were obtained from a multicenter registry of cryoballoon ablation for AF (n=2,689). Patients screened for typical atrial flutter were included in the analysis (n=1,907). All the patients with typical atrial flutter underwent CTI ablation. The primary endpoint was the late recurrence of atrial arrhythmia, including AF, atrial flutter, and atrial tachycardia. Among 1,907 patients, typical atrial flutter was detected in 493 patients (25.9%). Patients with concurrent atrial flutter had a lower incidence of persistent AF and a smaller left atrium. Patients with atrial flutter had significantly lower atrial arrhythmia recurrence (19.7 vs. 29.9%, p<0.001). In patients with atrial flutter, recurrence of atrial tachycardia or atrial flutter was more frequent (7.3 vs. 4.7%, p=0.028), but recurrence of AF was significantly lower (17.0 vs. 29.4%, p<0.001). Atrial flutter has been identified as an independent predictor of the primary endpoint (adjusted hazard ratio, 0.704; 95% confidence interval, 0.548–0.906; p=0.006). In patients with AF, typical atrial flutter may be a favorable marker of atrial arrhythmia recurrence, and CTI ablation in this population is associated with a lower recurrence of AF. Routine screening and ablation of coexisting atrial flutter may improve the clinical outcomes of AF.